Experimental investigation on combined sensible and latent heat storage in two different configurations of tank filled with PCM. (25th February 2019) - Lafri, D.; Semmar, D.; Hamid, A.; Ouzzane, M.
Highlights: Thermal heat storage used combined sensible and latent energy. Experimental study on a phenomenon of melting and solidification in PCM used as a medium for storage energy. Comparison between two different configurations of the storage medium disposition in a vertical tank. Longitudinal and radial temperature profiles inside the storage system. Abstract: For an efficient use of latent heat storage, it is necessary to know the phenomena that occur during the phase change from solid to liquid. This makes it possible to optimize the conditions that serve to reduce the charging and discharging time. The objective of this work is to study experimentally the process of heat transfer during the PCM (Phase Change Material) fusion. Two storage tanks of the same volume with a different filling positions of PCM are used in the setup. In the first tank, the paraffin is integrated directly in its lateral part, and in the second, the content of PCM is centered on the axis. It was observed that the total PCM melting in the first configuration lasts almost twice as long as in the second. Furthermore, the analysis of the thermal behavior of the storage has shown that the phase change during melting takes place on layers that are far from the exchange surface.